Improving the Quality of Kindergarten Education Through Ethnoscience-Based Teacher-Child Interaction for Children's Social-Emotional Development at State Kindergarten 1 Arongan Lambalek - Yulidar Yulidar; Lili Kasmini; Zahraini Zahraini (FKIP - Universitas Riau, 2026)
This research is motivated by the importance of strengthening the quality of early childhood education learning processes through contextual teacher-child interactions based on local wisdom. This study aims to analyze ethnoscience-based teacher-child interactions as an indicator of process quality and its impact on children's social and emotional development. This study uses a qualitative approach with a case study design. The research subjects consisted of teachers and children in group B at State Kindergarten 1 Arongan Lambalek. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation studies, while data analysis used an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that ethnoscience-based interactions implemented through role-playing activities and local cultural exploration can increase children's engagement, strengthen empathy, cooperation, and emotional regulation as part of the quality indicators of the learning process. This study concludes that ethnoscience-based teacher-child interactions can be integrated into the PPEPP quality assurance cycle as a pedagogical and managerial strategy to improve the quality of learning and children's social and emotional development in a sustainable manner.